The morphological diversity of Osedax worm borings (Annelida: Siboglinidae). (November 2014) - Higgs, Nicholas D.; Glover, Adrian G.; Dahlgren, Thomas G.; Smith, Craig R.; Fujiwara, Yoshihiro; Pradillon, Florence; Johnson, Shannon B.; Vrijenhoek, Robert C.; Little, Crispin T.S.
<x content-type="archive" xml:space="preserve">Abstract</x> Marine worms in the genus Osedax, have specialized 'root' tissues used to bore into the bones of decomposing vertebrate skeletons and obtain nutrition. We investigated the borings of nine Osedax species, using micro computed tomography to quantitatively describe the morphology of the borings and provide three-dimensional reconstructions of the space occupied by Osedax root tissues inside the bone. Each Osedax species displayed a consistent boring morphology in any given bone, but these differed between bones. In bones where multiple species coexisted there was limited evidence for spatial niche partitioning by Osedax root tissues inside the bones investigated here. The new morphological data may be applied to Osedax traces in fossil bones, showing that borings can be used to indicate minimum species richness in these bones.